2018
DOI: 10.1186/s13063-018-3013-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Ojeok-san in Korean female patients with cold hypersensitivity in the hands and feet: study protocol for a randomized, double-blinded, placebo-controlled, multicenter pilot study

Abstract: BackgroundThis study aims to evaluate the safety, efficacy, and feasibility of a full randomized clinical trial of Ojeok-san in Korean female patients with cold hypersensitivity in the hands and feet.MethodsThis study is a multicenter, double-blinded, randomized, placebo-controlled, two-arm, parallel-group pilot clinical trial. A total of 60 participants will be enrolled and randomly assigned to the Ojeok-san treatment group or the placebo control group, in a 1:1 ratio using an Internet-based randomization sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Several studies have been conducted to evaluate the e cacy and safety of Korean herbal medicines, including Danggui-SayukGa-Osuyu-Saenggang-tang [21], Ojeok-san [22], Sipjeondaebotang [23], Ucha-Shinki-Hwan [24], Onkyeong-tang [25], Korean Red Ginseng [26], for the treatment of CHHF. Studies of acupuncture or EA treatment for coldness have also been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted to evaluate the e cacy and safety of Korean herbal medicines, including Danggui-SayukGa-Osuyu-Saenggang-tang [21], Ojeok-san [22], Sipjeondaebotang [23], Ucha-Shinki-Hwan [24], Onkyeong-tang [25], Korean Red Ginseng [26], for the treatment of CHHF. Studies of acupuncture or EA treatment for coldness have also been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…First, ours is the rst RCT to assess the e cacy and safety of EA for the treatment of CHHF. There have been many RCTs to evaluate the effectiveness and safety of herbal medicines for the treatment of CHHF, but there have been no studies on the treatment of CHHF using EA or acupuncture.Second, the team members in our study had prior experience in RCTs related to CHHF, e.g., a pilot study of Danggui-SayukGa-Osuyu-Saenggang-tang [21], Ojeok-san [22], Sipjeondaebotang [23], Ucha-Shinki-Hwan [24], and Onkyeong-tang [25]; therefore, our study can be conducted more smoothly.…”
Section: Discussionmentioning
confidence: 99%
“…There were many studies on the effects of OKT on gynecological diseases and coldness, but there were no RCTs to examine the safety and efficacy of OKT for CHF. This study has another strength: specifically, the team members engaged in this clinical trial are familiar with the SOPs of this study, as they were part of a previous pilot study that investigated the effects of Danggui-SayukGa-Osuyu-Saenggang-tang [20], Ojeok-san [21], or Sipjeondaebo-tang [22] on CHHF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the components of the herbal extract, including Ag, Ac, and Zo, influences various malignant tumors, such as brain, breast, prostate, colorectal, skin, and pancreatic cancer ( Choi et al, 2016 ; Li et al, 2017 ; Nedungadi et al, 2019 ), various inflammatory diseases, and obesity and has neuroprotective effects( Semwal et al, 2015 ; Zhou et al, 2015 ; Sowndhararajan and Kim, 2017 ). Furthermore, extracts from a mixture of Ag, Ac, and Zo have been shown to effective various disease effect ( Kim et al, 2016 ; Ko et al, 2018 ; Han et al, 2019 ; Cheon and Ko, 2020 ; ).…”
Section: Introductionmentioning
confidence: 99%